ANALISIS GEOMETRIK DAN PERKERASAN JALAN DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) DAN AUTOCAD 3D PADA UNIVERSITAS KATOLIK INDONESIA SANTU PAULUS RUTENG - HASTI MEGANDARI; DANANG WIJANARKO (JURNAL DAKTILITAS, 2022)
Abstrack The road serves as a means of supporting academic activities within the Catholic University of antu Paulus Ruteng's campus area. Every year, the number of students grows, which has an effect on the ever-increasing number of vehicles. The ideal road lane width can be determined using geometric analysis in accordance with road geometric planning criteria. An analysis of the road capacity shows that segment 1 has a saturation level of 1,339, segment 2 has a saturation level of 0,571, segment 3 has a saturation level of 0.311, and segment 4 has a saturation level of 0,252. Analysis of the horizontal alignment of the eleven existing bends necessitates widening the pavement at the bends. Only segment 2 of the segment road geometric analysis that meets planning standards is segment 2. From the three methods of geometric analysis, a recommendation is made to improve the geometric of the road in the campus area of the Catholic University of Santu Paulus Ruteng. PI 1bend necessitates a pavement width of 1,390 meters; PI 2 bend 2,286 meters; PI 3 bend 3,495 meters; PI 4 bend 3,495 meters; PI 5 bend 3,495 meters; PI 6 bend necessitates a pavement width of 3,000 meters; 7 meters of road, 3.5 meters of lane, and 2.5 meters of sidewalk. Keywords: Road Geometric Analysis Abstrak Jalan berfungsi sebagai sarana penunjang kegiatan akademik di lingkungan kampus Universitas Katolik Santu Paulus Ruteng. Setiap tahunnya, jumlah mahasiswa terus bertambah, yang berimbas pada jumlah kendaraan yang terus meningkat. Lebar jalur jalan yang ideal dapat ditentukan dengan menggunakan analisis geometrik sesuai dengan kriteria perencanaan geometrik jalan. Analisis kapasitas jalan menunjukkan bahwa ruas 1 memiliki tingkat kejenuhan 1,339, ruas 2 memiliki tingkat kejenuhan 0,571, ruas 3 memiliki tingkat kejenuhan 0,311, dan ruas 4 memiliki tingkat kejenuhan 0,252. Analisis alinyemen horizontal dari sebelas belokan eksisting memerlukan pelebaran perkerasan pada belokan tersebut. Hanya segmen 2 dari analisis geometrikㅤ jalanㅤ segmenㅤ yangㅤmemenuhiㅤstandarㅤ perencanaanㅤadalah segmen 2. Dari ketigaㅤmetode analisisㅤgeometrik tersebut, dibuat rekomendasi perbaikan geometrik jalan di kawasan kampus Universitas Katolik Santu Paulus Ruteng. tikungan PI 1 membutuhkan lebar perkerasan 1.390 meter; tikungan PIㅤ2ㅤ2.286 meter; tikunganㅤPI 3 3.495 meter; tikungan PIㅤ4 3.495 meter; tikunganㅤPIㅤ5ㅤ3.495 meter; tikunganㅤPIㅤ6ㅤmembutuhkan lebar perkerasan 3.000 meter; Jalan 7 meter, lajurㅤ3,5 meter, dan trotoarㅤ2,5 meter. Kata Kunci: Analisis Geometrik Jalan